Comparison and Analysis of 3 Key AI Documents: EU's Proposed AI Act, Assessment List for Trustworthy AI (ALTAI), and ISO/IEC 42001 AI Management System - Golpayegani, Delaram; Pandit, Harshvardhan; Lewis, Dave (My University, 2022)
Conforming to multiple and sometimes conflicting guidelines, standards, and legislations regarding development, deployment, and governance of AI is a serious challenge for organisations. While the AI standards and regulations are both in early stages of development, it is prudent to avoid a highly-fragmented landscape and market confusion by finding out the gaps and resolving the potential conflicts. This paper provides an initial comparison of ISO/IEC 42001 AI management system standard with the EU trustworthy AI assessment list (ALTAI) and the proposed AI Act using an upper-level ontology for semantic interoperability between trustworthy AI documents with a focus on activities. The comparison is provided as an RDF resource graph to enable further enhancement and reuse in an extensible and interoperable manner.
30th Irish Conference on Artificial Intelligence and Cognitive Science (AICS)
Keywords: AI Act; Trustworthy AI; AI management system; ALTAI; ISO/IEC 42001; Ontology; Semantic web; AI standards; Research Subject Categories; AI Regulation; ARTIFICIAL INTELLIGENCE; SEMANTIC WEB; STANDARDS; trustworthy AI